PENGARUH PEMBERIAN AROMATERAPI CENDANA TERHADAP KEJADIAN INSOMNIA PADA IBU MENOPAUSE DI PMB ENY ISLAMIATI KECAMATAN BULULAWANG KABUPATEN MALANG - Nur Aulia Putri; Rani Safitri; Anik Sri Purwanti (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Introduction: Menopause is  a period of natural process towards aging which is characterized by the cessation of the menstrual cycle. Menopause occurs at the age of 45-55 years. The diagnosis of menopause can be established when menstruation stops for at least one year. Insomnia is a difficult state of initiating sleep, maintaining sleep, and sleep that is not refreshing. According to Gunadarma, the incidence of insomnia increases faster in mothers over the age of 40 years. About 40% of women aged 40-54 years complain of insomnia. Sandalwood aromatherapy is one of the complementary therapies that can also be used in overcoming the incidence of insomnia. The study was conducted at PMB Eny Islamiati Bululawang to examine the effects of sandalwood aromatherapy on incidence of insomnia in menopausal mother. Method: Pra experimental design. The study population was 20 menopausal mothers with a sample of 16 people. This technique uses purposive sampling. The instruments used by the KRSPBJ-IRS questionnaire and observation sheet, using the Wilxocon statistical test. Result: According to the data, there was significant incidence of insomnia in 43.6 percent of people prior to the intervention and mild incidence of insomnia in 75,0 percent of people after it, with a p value of 0.02 to α 0.05. Conclusion: Sandalwood aromatherapy may have an impact on the incidence of insomnia in the menopausal mother.It is hoped that menopausal mother  will be able to improve services both in health promotion such as socialization, counseling to menopausal mothers to provide health education about the importance of rest / sleep for menopausal mothers. Keywords: Aromatherapy Administration, Incidence of insomnia, Menopausal Mother